2019
DOI: 10.1021/acs.macromol.8b02659
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chain Primary Structure and Topology (Branching) on Crystallization and Thermal Properties: The Case of Polysulfides

Abstract: We have investigated how variations in primary structure (distribution of monomeric units, chain length) and degree of branching affect the crystallization behavior of polysulfides. In particular, we have used copolymers of crystallizable (ethylene sulfide, ES) and noncrystallizable (propylene sulfide, PS) units, prepared via anionic ringopening mechanism. PS units interrupt the crystallization of ES sequences; therefore, strong differences in thermal properties are expected between copolymers with a gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…The lower the value of Ts, the higher is the Tc upon cooling from the melt, indicating a stronger nucleation effect. This peculiar nucleation effect has been termed in different ways in the literature: crystalline memory 38,39,41,[56][57][58]61,63,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] , melt memory 49,52,60,64,[81][82][83][84][85][86][87][88][89][90][91][92][93][94] , in some works both terms are used indistinctly 18,47,48,62,65,[95][96][97][98] and in other cases a mo...…”
Section: Melt Memory As a Special Case Of Homogeneous Nucleationmentioning
confidence: 99%
“…The lower the value of Ts, the higher is the Tc upon cooling from the melt, indicating a stronger nucleation effect. This peculiar nucleation effect has been termed in different ways in the literature: crystalline memory 38,39,41,[56][57][58]61,63,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] , melt memory 49,52,60,64,[81][82][83][84][85][86][87][88][89][90][91][92][93][94] , in some works both terms are used indistinctly 18,47,48,62,65,[95][96][97][98] and in other cases a mo...…”
Section: Melt Memory As a Special Case Of Homogeneous Nucleationmentioning
confidence: 99%
“…For a given macromolecular structure, the slope of a versus graph is inversely related to its persistence length; all polymers produced in this study nicely fit with a single slope (Figure C), suggesting a negligible effect of branching. This is likely due to the long PLA chains (100 monomeric units per arm), which overcome the single branching point; this would not be the case for shorter chains, and indeed, we have recently showed that short-armed stars (polysulfides, 10–30 units per arm) have a larger persistence length than linear analogues …”
Section: Resultsmentioning
confidence: 99%
“…We then assessed the effect of branching and stereoregularity on hydrodynamic properties, first focusing on the Mark− Houwink parameter a. An a value of 0.5 indicates coils under theta (θ) conditions; lower valuestypically seen with increasing branching (see, e.g., with propylene sulfide homo-34 and copolymers 35 )reflect increasing contraction and lower propensity to entanglement; this trend was also recorded for PLAs (Figure 4A), which confirms their progressively lower tendency to entangle.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This distribution of melting points also reflects a distribution of lamellar thickness in the sample provoked by SSA thermal fractionation. This technique has been very useful to characterize ethylene/alfa-olefin copolymers, polypropylenes, block copolymers and more recently, segmented thermoplastic polyurethanes, recycled polyolefin blends, copolyesters and polysulfide based copolymers [39][40][41][42][43][44].…”
Section: Effect Of the Previous Standard State On The Self-nucleation Domains: Thickening Of Crystals By Successive Self-nucleation And Amentioning
confidence: 99%